Crystalline boron monosulfide nanosheets with tunable bandgaps. Issue 43 (27th October 2021) - Kusaka, Haruki; Ishibiki, Ryota; Toyoda, Masayuki; Fujita, Takeshi; Tokunaga, Tomoharu; Yamamoto, Akiyasu; Miyakawa, Masashi; Matsushita, Kyosuke; Miyazaki, Keisuke; Li, Linghui; Shinde, Satish Laxman; S. L. Lima, Mariana; et al.
Abstract : Two-dimensional boron monosulfide nanosheets are realized by physical exfoliation of rhombohedral boron monosulfide. Abstract : Two-dimensional (2D) boron monosulfide (BS) nanosheets are predicted to have several stable phases and unique electronic structures, endowing them with interesting attributes, including superconducting, thermoelectric, and hydrogen storage properties. In this paper, we report the experimental realization of 2D BS nanosheets by the physical exfoliation of rhombohedral boron monosulfide (r-BS). Moreover, we demonstrate the facile separation of a mixture of 2D BS nanosheets and the r-BS powder in acetonitrile; the former were selectively separated as a dispersion in the supernatant, whereas the latter remained in the precipitate. In addition, density functional theory calculations reveal a clear dependence of the bandgap energy ( E g ) on the number of layers of stacked BS nanosheets, where E g for BS nanosheets is approximately 1.0 eV higher than that for r-BS. Atomic force microscopy, cathode luminescence, ultraviolet-visible absorption spectroscopy, and excitation emission matrix experiments revealed a consistent bandgap difference of approximately 1.0 eV between the BS nanosheets and r-BS. We also demonstrate the applications based on the properties that originated from the difference in the bandgap between r-BS and BS nanosheets using photoelectrochemical current switching. These results indicate that the nanosheet bandgap can be tuned to a desired value by controlling the number of stacked 2D BS nanosheets. Therefore, BS nanosheets are promising non-metal 2D materials for applications requiring bandgap control, such as electronics and photocatalysis.